I don't know how to evaluate it. I know there is one method using the gamma function. BUT I want to know the solution using a calculus method like polar coordinates.

$$\int_{-\infty}^\infty x^2 e^{-x^2}\mathrm dx$$

I will wait for a solution. Thank you.

  • 38
    $\begingroup$ Every day I see someone here asking how to "solve" an integral. One does not "solve" integrals. One solves equations; one solves problems. One evaluates integrals. $\endgroup$ Sep 20 '11 at 16:56
  • 3
    $\begingroup$ I would say calculate or evaluated -- a problem is (if we are lucky) solved, an expression might sometimes be calculated. $\endgroup$
    – AD.
    Sep 20 '11 at 18:56
  • 1
    $\begingroup$ Here is a more general question. $\endgroup$ Sep 22 '11 at 12:11
  • $\begingroup$ Yes, you don't solve definite_ integrals, you evaluate them. $\endgroup$ Oct 18 '13 at 22:53
  • 1
    $\begingroup$ The question "How do I find $\int_{-\infty}^\infty e^{-x^2}\,dx$" has been asked and answered on this forum many times. I'm surprised so many people bothered to take the time to type a solution as part of the answer to your question when it has been done before. You can convert your integral to that one using integration by parts, with $dv = xe^{-x^2}dx$ and $u = x$. Also, J.M.'s link answers your question. $\endgroup$ Oct 18 '13 at 22:56

In order to solve the integral by polar coordinates first consider $I_s = \int_{-\infty}^\infty \mathrm{e}^{-s x^2} \mathrm{d} x$. The integral you seek will be obtained by differentiation as $-\left. \frac{\mathrm{d}}{\mathrm{d} s} I_s \right|_{s=1}$.

Now, to evaluate $I_s$:

$$ I_s^2 = \int_{-\infty}^\infty \mathrm{e}^{-s x^2} \mathrm{d} x \cdot \int_{-\infty}^\infty \mathrm{e}^{-s y^2} \mathrm{d} y = \int_{-\infty}^\infty \int_{-\infty}^\infty \mathrm{e}^{-s (x^2 + y^2)} \, \mathrm{d} x \mathrm{d} y $$ Now change variables into polar coordinates $x = r \sin \theta$ and $y = r \cos \theta$. $$ I_s^2 = \int_{0}^{2 \pi} \mathrm{d} \theta \int_0^\infty \mathrm{e}^{-s r^2} \cdot r \, \mathrm{d} r = \pi \int_0^\infty \mathrm{e}^{-s t} \mathrm{d} t = \frac{\pi}{s} $$ where $t = r^2$ change of variable has been made.

Now, since $I_s > 0$ for $s >0$, we obtain $I_s = \sqrt{\frac{\pi}{s}}$.

The integral in question now follows: $$ \int_{-\infty}^\infty x^2 \mathrm{e}^{-x^2} \mathrm{d} x = \left. -\frac{\mathrm{d}}{\mathrm{d} s} \sqrt{\frac{\pi}{s}} \right|_{s=1} = \left. \frac{\sqrt{\pi}}{2} s^{-\frac{3}{2}} \right|_{s=1} = \frac{\sqrt{\pi}}{2} $$

  • 3
    $\begingroup$ Very nice indeed! A solution that yields the value of $\int_{-\infty}^{\infty} x^{2n} e^{-x^2} \mathrm dx$ upon differentiating $n$ times with respect to $s$ and setting $s = 1$... $\endgroup$ Sep 20 '11 at 15:21

(As the OP wants a solution without using the gamma function.) Following Davide's suggestion, we write: $$ \int_{-\infty}^{\infty} x^2 e^{-x^2} dx = -\frac{1}{2}\int_{-\infty}^{\infty} x \cdot (-2x e^{-x^2}) dx. $$ Let $u = x$ and $v = e^{-x^2}$. We have $\frac{dv}{dx} = -2xe^{-x^2}$. Integrating by parts: $$ -\frac{1}{2}\int_{-\infty}^{\infty} u \frac{dv}{dx} dx = -\frac{1}{2} \left. uv \right|_{-\infty}^{\infty} + \frac{1}{2} \int_{-\infty}^{\infty} v \frac{du}{dx} dx. $$ I will leave it as an exercise to compute the first term. (Hint: it should come out to $0$. :)) The integral appearing in the second term (ignoring the factor of $\frac{1}{2}$ in the front) simplifies to: $$ \int_{-\infty}^{\infty} v \frac{du}{dx} dx = \int_{-\infty}^{\infty} e^{-x^2} dx. $$ This is the famous Gaussian integral, whose value is $\sqrt{\pi}$. You should now be able to evaluate integral easily.

  • 1
    $\begingroup$ [For those who had trouble solving hint] First part can be reduced to $\lim_{a\to 0} a\sqrt{ln(1/a)}$ by substituting $a = e^{-x^{2}}$ which can be further reduced to $\lim_{a\to 0^{+}} \sqrt{ln(1/a^{2})/2*a^{2}}$ and since we know that $\lim_{x\to 0} ln(1/x)/x = 0$, the previous also evaluates to zero. $\endgroup$ Feb 14 '17 at 20:35
  • $\begingroup$ [For those who had trouble solving hint] an alternative way of evaluating the term which in intended to be zero, is to acknowledge that if $f(x) = xe^{-x^2}$ then $f(-x) = (-x)e^{-(-x)^2} = -f(x)$, or in other words, the term represents a integral over an symmetric interval, and thus, its 0. $\endgroup$
    – JustDanyul
    Mar 13 '19 at 20:26
  • $\begingroup$ @JustDanyul I think that's not correct, since inside the vertical bar f(x) isn't approaching +inf and -inf at the same speed. Actually if f(x) diverges approaching +inf and -inf, the result would diverge. The same reason why $$x^3|^{\infty}_{-\infty}$$ diverges. $\endgroup$
    – Hot.PxL
    May 4 '20 at 12:43

Detailing Srivatsan Narayanan's solution. It is known that the functional equation of the gamma function may be derived applying the integration by parts technique. Its value at $1/2$ may be evaluated by computing a double integral over the first quadrant in Cartesian and polar coordinates. Let's apply similar ideas in this case. Let $f(x)=x^{2}e^{-x^{2}}$. Since $ f(-x)=f(x)$ the integral $\int_{-\infty }^{\infty }f(x)\mathrm{d}x=2\int_{0}^{\infty }f(x)\mathrm{d}x$. Integrating by parts $$ \int x^{2}e^{-x^{2}}\mathrm{d}x=\int x\cdot xe^{-x^{2}}\mathrm{d}x, $$ since $$ \int xe^{-x^{2}}\mathrm{d}x=-\frac{1}{2}e^{-x^{2}} $$ and $\frac{dx}{dx}=1$, we get $$\begin{eqnarray*} \int x^{2}e^{-x^{2}}\mathrm{d}x &=&x\left( -\frac{1}{2}e^{-x^{2}}\right) -\int -\frac{ 1}{2}e^{-x^{2}}\,\mathrm{d}x \\ &=&-\frac{1}{2}xe^{-x^{2}}+\frac{1}{2}\int e^{-x^{2}}\,\mathrm{d}x.\tag{0} \end{eqnarray*}$$

And so, $$\begin{eqnarray*} \int_{0}^{\infty }x^{2}e^{-x^{2}}dx &=&\left. -\frac{1}{2} xe^{-x^{2}}\right\vert _{0}^{\infty }+\frac{1}{2}\int_{0}^{\infty }e^{-x^{2}}\,\mathrm{d}x \\ &=&\left( \lim_{c\rightarrow \infty }-\frac{1}{2}ce^{-c^{2}}\right) +\frac{1 }{2}0e^{-0^{2}}+\frac{1}{2}\int_{0}^{\infty }e^{-x^{2}}\,\mathrm{d}x \\ &=&0+0+\frac{1}{2}\int_{0}^{\infty }e^{-x^{2}}\,\mathrm{d}x \\ &=&\frac{1}{2}\int_{0}^{\infty }e^{-x^{2}}\,\mathrm{d}x.\tag{1} \end{eqnarray*}$$

Consequently, $$ I:=\int_{-\infty }^{\infty }x^{2}e^{-x^{2}}\mathrm{d}x=2\int_{0}^{\infty }x^{2}e^{-x^{2}}\mathrm{d}x=\int_{0}^{\infty }e^{-x^{2}}\,\mathrm{d}x.\tag{2} $$

To evaluate this last integral we compute the following double integral in Cartesian and polar coordinates ($r^{2}=x^{2}+y^{2}$, $x=r\cos \theta ,y=r\sin \theta $). Since the Jacobian of the transformation $\frac{\partial (x,y)}{\partial (r,\theta )}=r$, we have $$ \int_{x=0}^{\infty }\int_{y=0}^{\infty }e^{-x^{2}-y^{2}}\mathrm{d}x\mathrm{d}y=\int_{\theta =0}^{\pi /2}\int_{r=0}^{\infty }e^{-r^{2}}r\mathrm{d}r\mathrm{d}\theta.\tag{3} $$ Comparing the LHS $$ \int_{x=0}^{\infty }\int_{y=0}^{\infty }e^{-x^{2}-y^{2}}\mathrm{d}x\mathrm{d}y=\left( \int_{0}^{\infty }e^{-x^{2}}\mathrm{d}x\right) \left( \int_{0}^{\infty }e^{-y^{2}}\mathrm{d}y\right) =I^{2}\tag{4} $$ with the RHS $$\begin{eqnarray*} I^2 &=&\int_{\theta =0}^{\pi /2}\int_{r=0}^{\infty }e^{-r^{2}}r\mathrm{d}r\mathrm{d}\theta = \frac{\pi }{2}\int_{0}^{\infty }e^{-r^{2}}r\mathrm{d}r \\ &=&\frac{\pi }{2}\left. \left( -\frac{1}{2}e^{-r^{2}}\right) \right\vert _{0}^{\infty }=\frac{\pi }{2}\left( \lim_{c\rightarrow \infty }-\frac{1}{2} e^{-c^{2}}+\frac{1}{2}e^{-0^{2}}\right) \\ &=&\frac{\pi }{2}\left( 0+\frac{1}{2}\right) =\frac{\pi }{4},\tag{5} \end{eqnarray*}$$ yields $$ I=\frac{\sqrt{\pi }}{2}.\tag{6} $$


First, since the integrand is symmetric around $0$, we can write it as twice the integral from $0$ to $\infty$. Now, change variables by letting $u=x^2$ so that $du=2xdx$. Then our integral becomes $$\int_{-\infty}^\infty x^2e^{-x^2} dx=\int_{0}^\infty xe^{-x^2} 2xdx=\int_{0}^\infty u^{\frac{1}{2}} e^{-u}du=\Gamma\left(\frac{3}{2}\right) =\frac{\sqrt{\pi}}{2}$$ by the definition of the Gamma function along with the fact that $\Gamma(1/2)=\sqrt{\pi}$. (7 proofs of this last identity, or equivalently the identity $\int_{-\infty}^\infty e^{-x^2}dx =\sqrt{\pi}$ are given on this Math Stack Exchange post.)

  • $\begingroup$ Thank you. But I want to know solution not using gamma function. $\endgroup$ Sep 20 '11 at 14:40
  • 7
    $\begingroup$ @Kim: In any case, you will need to use the fact that $\int_{-\infty}^\infty e^{-x^2}dx =\sqrt{\pi}$. This integral by a change of variables is the same as $\Gamma(1/2)$. Any solution will implicitly be using or proving facts about the Gamma function. $\endgroup$ Sep 20 '11 at 14:42

If you know that $\int_{-\infty}^\infty e^{-x^2}=\sqrt\pi$, then you can use it to easily solve this.

Differentiating $e^{-x^2}$ twice,


Now integral of the left hand side is $0$, as $\int\left(\frac{d^2}{dx^2}e^{-x^2}\right)dx=\frac{d^2}{dx^2}\int e^{-x^2}dx=\frac{d^2}{dx^2}\sqrt\pi=0$.

So integrating, we get

$$\begin{array}{rcl} 0&=&\int -2e^{-x^2}+4x^2e^{-x^2}\,dx\\ &=&-2\sqrt\pi+4\int x^2e^{-x^2}\,dx\\ \implies\int x^2e^{-x^2}\,dx&=&\frac{\sqrt\pi}{2} \end{array} $$


Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.